Fluvial network of water burning basin as landscape-geochemical arene of pollution and self-inspection - Karpets, K. M. (Man and Environment. Issues of Neoecology, 2017)
Purpose. To evaluate the possibilities of self-purification of the fluvial network of the catchment basin from the point of view of landscape geochemical properties of the sub-bodies of lower orders. Results. Considering the processes and phenomena of technogenic pollution within the limits of the geographical landscape, within the framework of certain research generalizations of the boundary of the landscape can be considered a direct result of the spatial patterns of interaction between the two main factors of landscape dynamics and development - the flyuvial relief and hydrological regime of the territory. Under the fluvial geomorphological system, we understand the geomorphosystem of the fluvial functional-genetic series. The latter is a model of a certain ontological essence, an actual geosystem (the natural system) - the hydro-geomorphological system of the catchment [8], the elements of which are combined into a spatial-functional whole, precisely because of the fluvial process - the genetic type of the general process of relief formation, which, within the framework of the limitotrophic subject industry, hydro-geomorphological process. Conclusions. The water basin can be considered as a geosystem, it follows from the fact that the main characteristics of the fluvial water catchment network are determined by the ability to spontaneously organize within its boundaries subquests of lower orders. Fluvial network is one of the most important evaluation indicators, as it contributes to the redistribution of energy and substances in the system of interaction of natural components. It is the fluvial network that determines the degree of drainage, the intensity of erosion processes and the direction of surface runoff. To assess the self-cleaning of the catchment basin, the following characteristics of the relief of its surface are significant, such as the depth of vertical dismemberment and steepness of the slopes, which determine the direction of the flow of matter and the capacity of the catchment for self-purification. The higher the value of these parameters and the greater the speed of the surface runoff, the much greater capacity of the catchment to self-purification.